Pengembangan Kurikulum Ismuba Di SMP Muhammadiyah Muntilan - Rafik Tri Hardian; Hendro Widodo (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
This study is related to ISMUBA curriculum development. Referring to the problems faced by the world of education in the era of globalization and rapidly devel oping technology, the curriculum in education is very important to create a productive, efficient and creative learning process. The purpose of this study was to determine ISMUBA curriculum development in the teaching and learning process. This research is a field research with a qualitative approach. Data collection techniques using interviews, observation and summaries. Data analysis was carried out through data reduction, reduction, and data processing according to the research objectives. Based on the results of the research, the use of the curriculum at SMP Muhammadiyah Muntilan uses the ISMUBA curriculum from the Muhammadiyah Central Board of Elementary and Secondary Education. ISMUBA curriculum development is carried out on two sides, namely in the ISMUBA Practice Project school, Student Assessment Pause Contest, Hisbul Wathon, Tapak Suci, Dzuhur and Azar Prayer Worship Activities, and Gitarmu (Active Ramadan SMP Muhammadiyah Muntilan) and outside of school such as practical application Worship services that have been trained (Fardhu Prayers, Sunaah Prayers, Funeral Prayers and Thaharah), Koran at each other's homes, visiting sick people, distribution of sacrificial animals and competitions outside of school and other activities that support ISMUBA education. But the inhibiting factors in the curriculum require teacher evaluation and open book facilities to always improve the learning process and increase interest in literacy